A Study to Evaluate the Effectiveness of Various Disinfectants for Extracted Human Teeth - A Comparative Study - Himanshu Srivastava; Sameera Mohd Rehman Qureshi; Chintu Kumar Singh; Santoshkumar Pandurang Mastud; Amit Handa; Manish Kumar Shukla (Indian Journal of Dental Research)
Objectives: The aim of this study was to evaluate the effectiveness of various disinfectants for extracting human teeth. The objectives were to assess the effectiveness of 5% vinegar, 3% hydrogen peroxide, 70% alcohol, and 5.25% sodium hypochlorite for disinfection of extracted human teeth. Methods: The teeth were divided into one of the following four groups consisting of 10 teeth in each group. All teeth were immersed in separate bottles containing 10 ml of the disinfectant for 7 days at 25°C. No visible growth in the broth was considered effective disinfection. The Institutional Ethics Committee (IEC) Number is SVIEC/ON/DENT/SRP/15186, and the IEC Clearance number is SVIEC/ON/DENT/SRP/15040. Results: Vinegar was most effective for bacterial disinfection, and 5.25% sodium hypochlorite was most effective for fungal disinfection. The result was statistically significant with Chi-square values of 0.015 and 0.057, respectively, and P < 0.001. Conclusions: Extracted teeth should be handled with extreme care as these are a potential source of infection. The present study documented the role of various disinfectants. Vinegar can be used as an effective disinfectant medium for extracting human teeth. Sterilisation and autoclaving are superior options while vinegar is cheap, readily available, and relatively non-toxic. All these qualities plus the fact that it has given encouraging results as an antibacterial disinfectant should necessitate its usage on a more regular basis than it is used at present.